Max Weber’s Concept and Theory of Charisma in the Reception of Social and Historical Sciences - Rychterová, Pavlína (Dějiny – teorie – kritika, 2006)
The notion of charismatic authority and charismatic leadership, as developed in the writings of Max Weber, remains a controversial topic in the social sciences. This article discusses selected instances of the impact of this concept, particularly in relation to the historical sciences. The term charisma itself has been problematized from the beginning, especially in its original meaning as a gift of God - which was based on the New Testament and especially the Epistles of Paul. Further difficulties have arisen from the contemporary use of the term, as with the development of modern media the term charisma has infiltrated newspeak, the language of commercial and political marketing, and the pseudo-scientific jargon of popular psychological-esoteric educational literature. In contemporary sociology and historical scholarship, the response to Weber's notion of charisma falls between these two poles. More recently, the question of charismatically legitimated authority has been taken up by medievalists and is proving fruitful in many areas.